Evaluating the economic impact of national sporting performance: Evidence from the Johannesburg Stock Exchange - B. K. Smith; J. D. Krige (South African Journal of Business Management, 2010)
This study examines the impact of South Africa's national soccer, rugby and cricket teams' performances in international matches on returns on the Johannesburg Stock Exchange (JSE). Match results constitute a mood proxy variable hypothesised to affect stock returns through its influence on investor mood. The unconditional mean return on the JSE All Share index for a 13 year period from September 1995 to February 2009 was compared to the mean return after wins, draws and losses by the national sport teams. An event study approach was followed and four different statistical tests were conducted in order to test for a relationship. The results of the tests indicate the existence of a moderate win effect, with mean returns after wins being statistically significantly higher for the categories all sports combined, cricket and soccer.
Keywords: 650